Firm Size Moderates the Effect of Tax Planning and Sales Growth on Firm Value - Anggita Dwi Lestari; Suripto (Universitas Pendidikan Ganesha, 2026)
This study aims to examine the effect of tax planning and sales growth on firm value, as well as to analyze the role of firm size as a moderating variable in that relationship. The research object consists of coal sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. The sampling method used is purposive sampling, resulting in 18 companies with a total of 90 observations. The data analysis technique employs panel data regression with the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) approaches, along with Moderated Regression Analysis (MRA) to test the moderation effect. The dependent variable in this study is firm value proxied by Price to Book Value (PBV), the independent variables consist of tax planning proxied by the Effective Tax Rate (ETR) and sales growth, while firm size proxied by the natural logarithm of total assets serves as the moderating variable. The results indicate that: (1) tax planning has a significant negative effect on firm value; (2) sales growth has no effect on firm value; (3) firm size is unable to moderate the effect of tax planning on firm value; and (4) firm size is unable to moderate the effect of sales growth on firm value. The MRA results indicate that firm size falls into the category of homologizer moderator. This study is grounded in signaling theory and agency theory as the theoretical framework. Keywords: tax planning, sales growth, firm value, firm size, moderation.